2003
DOI: 10.1002/smi.959
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the relationship between job satisfaction and employee health in Hong Kong

Abstract: A meta-analysis was conducted of correlations between job satisfaction and measures of health for samples originating from Hong Kong. Using established procedures and a priori selection criteria, 22 samples were combined from published and unpublished sources, in a combined sample of 4492 workers from various industries and occupations. Results indicated relationships between job satisfaction and health for Hong Kong employees were high, and notably different from the larger sample in the HERMES study (Cass, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 101 publications
2
48
1
2
Order By: Relevance
“…The influence of job dissatisfaction on commitment was not found. This finding is contrary to previous evidence (Cass et al ., 2003) that job stressors have negative effect on employees' commitment to the organisation. It implies that job satisfaction does not affect commitment and health and wellbeing in the Chinese higher education sector.…”
Section: Implications For Higher Education Managementcontrasting
confidence: 99%
“…The influence of job dissatisfaction on commitment was not found. This finding is contrary to previous evidence (Cass et al ., 2003) that job stressors have negative effect on employees' commitment to the organisation. It implies that job satisfaction does not affect commitment and health and wellbeing in the Chinese higher education sector.…”
Section: Implications For Higher Education Managementcontrasting
confidence: 99%
“…Linking psychological strain to job satisfaction The relationship between stress/strain and job satisfaction is well established in the research literature (e.g. Cooper et al, 1989;Burke, 2001;Cass et al, 2003;Wang et al, 2014), although there is considerable debate about the direction of causality in this relationship, with job satisfaction reported in different studies to be either an antecedent, mediator, or outcome of job stress. No studies were found that explored this relationship within the telework literature.…”
Section: Introductionmentioning
confidence: 96%
“…A workplace environment characterised by such empowerment strategies can improve productivity as well as cohesion and job satisfaction for the employees [26,27]. The relation between health outcome and job satisfaction has been confirmed [28], and job satisfaction among nursing staff has been found to be positively correlated with transformational leadership style [29]. …”
Section: Introductionmentioning
confidence: 99%